Konsep Pendidikan Bermutu dalam Perspektif Pendidikan Islam - Agus Triyono; Meti Fatimah (TSAQOFAH, 2026)
Quality education is not only oriented toward academic achievement but also encompasses the holistic development of students in intellectual, emotional, social, and spiritual aspects. This study aimed to analyze the concept of quality education from the perspective of Islamic education. The study employed a qualitative approach using library research through the examination of books, scholarly journals, and classical and contemporary Islamic literature. The results showed that the concept of quality education generally emphasizes the integration of inputs, processes, and outputs to produce competent and competitive graduates. From the perspective of Islamic education, quality education has a more comprehensive scope because it integrates divine values derived from the Qur’an and Hadith. Quality education is directed toward developing individuals who are not only knowledgeable but also possess strong faith and noble character through a balance among faith, knowledge, and righteous action. Indicators of educational quality encompass not only academic achievement but also students’ character, discipline, and social responsibility. This study concludes that integrating modern concepts of educational quality with Islamic values establishes an educational framework that balances worldly and afterlife-oriented needs. These findings contribute to the development of a holistic educational concept relevant to forming a generation that is intelligent, faithful, morally upright, and capable of addressing educational challenges in the modern era.